The effect of different levels of Valine in low protein diets on cellular and humoral immunity of broiler chickens - Khosrow Parsaeimehr (Islamic Azad University, Tabriz Branch, 2021)
Different levels of valine in low protein diets have a significant effect on the immune system of broiler chickens. This experiment was performed to evaluate the effect of different levels of valine in low protein diets on the immune response of broiler chickens. This study was conducted using 200 one-day old male broilers of Ross 308 strain in a completely randomized design with 5 replicates and 10 birds per replicate. Experimental treatments were adjusted based on the Brazilian tables and included: control diet with recommended levels of valine, 10% higher than the recommended level of valine and 20% higher than the recommended level of valine diluted in a diet containing 2% protein. The results showed that different levels of valine had no significant effect on the weight of liver, spleen, fabricius bursa and leukocytes (p<0.05). Diets containing 20% valine significantly increased the HI antibody and humoral immunity responses (p<0.05). The initial total antibody response was not affected by the experimental treatments (p<0.05). But the level of 20% valine significantly increased the total secondary response and IgM secondary response to SRBC (p<0.05). Moreover the addition of valine had a significant effect on the injection reaction of PHA-P (p<0.05), and level of 20% valine, significantly increased the cellular immunity of broilers in comparison to the control treatment and lower valine levels. In the present study, the addition of high levels of valine in low-protein diets improved the cellular and humoral immunity of broiler chickens.